2001
DOI: 10.1046/j.1442-200x.2001.01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell lysis syndrome resulting from transient abnormal myelopoiesis in a neonate with Down’s syndrome

Abstract: Newborns with Down's syndrome occasionally present with transient proliferation of blasts, designated as transient abnormal myelopoiesis (TAM) 1 or transient myeloproliferative disorder. The blasts have monoclonality and a megakaryocyte nature with the capacity to differentiate towards multilineage blood cells. 2 The disorder is assumed to be different from 'true malignancy', because the disease regresses spontaneously. However several complications, including hyperviscosity syndrome, hemorrhage and liver fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…There are few reports of TLS associated with TAM. Kato et al reported one patient with TAM who developed TLS 6 . The present case was complicated by acute renal failure, which was induced by asphyxia.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…There are few reports of TLS associated with TAM. Kato et al reported one patient with TAM who developed TLS 6 . The present case was complicated by acute renal failure, which was induced by asphyxia.…”
Section: Discussionmentioning
confidence: 57%
“…The most commonly associated malignancies are non‐Hodgkin’s lymphoma and acute lymphocytic leukemia 4,5 . TLS is rarely reported in association with TAM 6 …”
mentioning
confidence: 99%
“…Kato et al reported one patient with TAM who developed TLS. 6 The present case was complicated by acute renal failure, which was induced by asphyxia. However, blood chemistry fi ndings revealed increasing levels of serum IP, potassium and UA together with a decrease in the number of blasts.…”
Section: Discussionmentioning
confidence: 74%
“…These metabolic complications include hyperkalemia, hyperphosphatemia, hyperuricemia and hyperuricosuria, hypocalcemia, and consequent acute uric acid nephropathy and acute renal failure [7]. There are only few reports of TLS associated with TMD [10,11]. Abe et al .…”
Section: Discussionmentioning
confidence: 99%
“…Kato et al . reported the case of a baby with DS who developed TLS as a result of TMD, successfully treated with allopurinol and diuretics [10]. …”
Section: Discussionmentioning
confidence: 99%